1996
DOI: 10.1111/j.1558-5646.1996.tb03609.x
|View full text |Cite|
|
Sign up to set email alerts
|

HIERARCHICAL ANALYSIS OF INBREEDING DEPRESSION IN PEROMYSCUS POLIONOTUS

Abstract: Abstract.-The severity of inbreeding depression appears to vary among taxa, but few ecological or other patterns have been identified that predict accurately which taxa are most sensitive to inbreeding. To examine the causes of heterogeneity in inbreeding depression, the effects of inbreeding on reproduction, survival, and growth were measured in three replicate experimental stocks for each of three subspecies of Peromyscus polionotus mice. Inbreeding of the dam reduced the probability of breeding, the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 49 publications
5
143
0
Order By: Relevance
“…This is apparent when estimating the effects of inbreeding on male and female fitness (e.g., female fecundity and male fertility; Fry et al 1998). However, it is not uncommon to find that inbreeding may have drastic effects on particular fitness measures while no significant effects on others (Lacy et al 1996). As a general rule, there seems to be little correlation on the effects of inbreeding among different fitness trait components (Kuke Bijlsma, personal communication).…”
Section: Drift Effects On Multiple Trait Componentsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is apparent when estimating the effects of inbreeding on male and female fitness (e.g., female fecundity and male fertility; Fry et al 1998). However, it is not uncommon to find that inbreeding may have drastic effects on particular fitness measures while no significant effects on others (Lacy et al 1996). As a general rule, there seems to be little correlation on the effects of inbreeding among different fitness trait components (Kuke Bijlsma, personal communication).…”
Section: Drift Effects On Multiple Trait Componentsmentioning
confidence: 96%
“…Under the detrimental paradigm of inbreeding depression (upper pathway), arrows presuppose a consistent an unambiguous relationship between population size, genetic diversity, fitness and extinction risks fitness. Classic studies by Pray and Goodnight (1995) and Wade et al (1996) on Tribolium castaneum, Lacy et al (1996) on Peromyscus polionotus, and Holtsford (1996) on Clarkia have shown population-specific effects of bottlenecks on inbreeding depression. That is, while some populations showed signs of decreased genetic diversity and inbreeding depression, others revealed no declines or even increases in genetic variation and fitness following bottlenecks.…”
Section: The Detrimental Paradigm Of Inbreeding Depressionmentioning
confidence: 98%
“…Note that d includes both the Mendelian sampling variability and the ignorance about the knowledge of the parents. Lacy et al (1996) and Lacy (1997) described how to decompose an inbreeding coefficient in several parts attributable to each population founder. The method presented here makes use of the same procedure, allowing a complete decomposition of the inbreeding coefficients or the coancestries, including the effects of the non-founder animals.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Lacy et al (1996) suggested a different partition for both inbreeding and coancestries as partial components due to each founder. The sum, across all founders, of the partial inbreeding coefficients for an individual is equal to the overall inbreeding for that individual.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation